2018
DOI: 10.25259/ajs-33-2018
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Blood Flow in the Testis: Is it Testicular Torsion?

Abstract: The absence of blood flow in the testis on ultrasound examination is the gold standard for diagnosis of testicular torsion. This imaging finding is seen in the vast majority of patients with testicular torsion, except in patients with partial torsion. Patients with partial testicular torsion may have reversal of arterial diastolic flow on spectral Doppler, decreased amplitude of the spectral Doppler waveform (parvus tardus wave), or monophasic waveforms. However, it is important to consider that not all absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It has been reported that sensitivity and specificity of color Doppler USG were 96-100% and 84-100% in diagnosis of torsion, respectively (16,17). Nuclear testicular flow studies performed as another technique for evaluation of blood flow of the testicles are not currently preferred since it is a long-lasting procedure and also not always available (18). The popularity of color Doppler USG has progressively increased because it is a non-invasive procedure and contributes to accurate diagnosis at least as much as nuclear scan.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that sensitivity and specificity of color Doppler USG were 96-100% and 84-100% in diagnosis of torsion, respectively (16,17). Nuclear testicular flow studies performed as another technique for evaluation of blood flow of the testicles are not currently preferred since it is a long-lasting procedure and also not always available (18). The popularity of color Doppler USG has progressively increased because it is a non-invasive procedure and contributes to accurate diagnosis at least as much as nuclear scan.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the interstitial tissue is affected, leading to decreased levels of testosterone production by Leydig cells. Eventually, these pathological processes lead to testicular inflammation (Forrest et al., 2018). Any factor which inhibits the inflammation and increases the antioxidant level of cells can lead to the elimination of pathological complications and return the abnormal status of the testis to its normal and physiological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Note that an absence of Doppler signal within the testis is most commonly due to the spermatic cord's twisting. However, there are other potential etiologies for testicular ischemia, including vasculitis, drug‐mediated vasoconstriction, inguinal hernia or following inguinal hernia repair, and severe infection that is not responding to antibiotic therapy 25,26 . In these settings, the clinical history is of utmost importance.…”
Section: Torsionmentioning
confidence: 99%